PEMAKNAAN PEMILIH PEMULA DALAM KAMPANYE DIGITAL PRABOWO-GIBRAN PADA PILPRES 2024 - Amaliah, Sitti Nur; Rohmawati, Yuning Ika (Universitas Gunadarma, 2024)
The Presidential Election (Pilpres) in 2024 is an essential political event and is a highly anticipated moment for the Indonesian people in determining the country's leader for the next five years. From the number of voters recorded in the Permanent Voter List (DPT), it is estimated that in the 2024 election, the vote will be dominated by those from the millennial and Z generations (17-43 years old). In the technology-based era, digital political campaigns are the main focus in communicating with voters and influencing their decisions. This study aims to analyze the meaning of novice voters and provide an overview of how they respond to the Prabowo-Gibran pair's digital campaign in the context of the 2024 Presidential Election through a reception analysis method. This research uses an interpretive paradigm through a qualitative approach with reception theory by Stuart Hall. Data were obtained through observation, interviews with novice voters and documentation. The research shows that there is a variation in the meaning of novice voters in the digital campaign. Most novice voters responded positively (dominant hegemonic position), finding digital campaigns effective in shaping positive perceptions and influencing political views. However, there are also novice voters who accept some of the ideology but reject its implementation (negotiated position), and who reject the overall campaign message (oppositional position).